BRCA1 and STMN1 as prognostic markers in NSCLCs who received cisplatin-based adjuvant chemotherapy - Wang, Mingxing (Oncotarget, 2017)
OBJECTIVE: In this study, we aimed to investigate the predictive effect of BRCA1, STMN1, MAPT and TUBB3 on the prognosis of patients with non-small cell lung cancer (NSCLC). METHODS: Seventy NSCLC patients who received platinum-based chemotherapy from June 2009 to July 2011 were enrolled. The protein and mRNA levels of BRCA1, STMN1, MAPT and TUBB3 were determined. Survival time of the patients with NSCLC was also calculated. RESULTS: High expression of BRCA1 or low expression of STMN1 was associated with a better prognosis in NSCLC patients (p<0.01). In contrast, the expression of MAPT and TUBB3 were not closely related with the prognosis of NSCLC patients(p>0.05). Furthermore, patients with high expression of BRCA1 and low expression of STMN1 have lived longer (p<0.01). CONCLUSION: BRCA1 and STMN1 were independently predictors for prognosis of NSCLCs which received cisplatin-based adjuvant chemotherapy.